2020
DOI: 10.1021/acs.nanolett.0c00800
|View full text |Cite
|
Sign up to set email alerts
|

Thermogalvanic Hydrogel for Synchronous Evaporative Cooling and Low-Grade Heat Energy Harvesting

Abstract: Efficient heat removal and recovery are two conflicting processes that are difficult to achieve simultaneously. Here, in this work, we pave a new way to achieve this through the use of a smart thermogalvanic hydrogel film, in which the ions and water undergo two separate thermodynamic cycles: thermogalvanic reaction and water-to-vapor phase transition. When the hydrogel is attached to a heat source, it can achieve efficient evaporative cooling while simultaneously converting a portion of the waste heat into el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
131
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 192 publications
(135 citation statements)
references
References 31 publications
3
131
0
1
Order By: Relevance
“…The long-term P MAX /∆T 2 of our optimized device is comparable with reported gel electrolyte systems. [19,23,25,45] Once the p-type cell electrode was optimized, electrodes suitable for use with our developed PVA-FeCl 2/3 electrolytes (n-type) were investigated, with a target of reaching comparable performance to the p-type configuration. Surprisingly, it was found that the single component film electrode of PEDOT/PSS exhibited superior performance surpassing all the other studied carbon-based materials including PEDOT/PSS-EFG, PEDOT/ PSS-CNT, and PEDOT/PSS-EFG/CNT ( Figure S10a, Supporting Information).…”
Section: Electrode Optimization For P-and N-type Cellsmentioning
confidence: 99%
“…The long-term P MAX /∆T 2 of our optimized device is comparable with reported gel electrolyte systems. [19,23,25,45] Once the p-type cell electrode was optimized, electrodes suitable for use with our developed PVA-FeCl 2/3 electrolytes (n-type) were investigated, with a target of reaching comparable performance to the p-type configuration. Surprisingly, it was found that the single component film electrode of PEDOT/PSS exhibited superior performance surpassing all the other studied carbon-based materials including PEDOT/PSS-EFG, PEDOT/ PSS-CNT, and PEDOT/PSS-EFG/CNT ( Figure S10a, Supporting Information).…”
Section: Electrode Optimization For P-and N-type Cellsmentioning
confidence: 99%
“…However, the low conductivity factor (i.e., the ratio of electrical and thermal conductivity) of the electrolytes leads to poor thermoelectric performance. [ 5 ]…”
Section: Figurementioning
confidence: 99%
“…TENGs is feasible for driving various electronic devices, ranging from light-emitting diodes (LEDs) (Yang et al, 2013d ; Lin et al, 2014 ; Chun et al, 2015 ; Kanik et al, 2015 ; Mao et al, 2015 ; Wu et al, 2016 ) to cell phones (Wang et al, 2012 ; Zhu et al, 2014c ) and from a large number of bio-sensors (Fan et al, 2015 ; Wen et al, 2015 ; Cai et al, 2018 ; Su et al, 2018 , 2020a , b ; Davoodi et al, 2020 ; Meng et al, 2020 ) to pacemakers (Zheng Q. et al, 2014 ). This shows showing their remarkable compatibility with a wide range of application in different settings, displaying that plentiful possibilities are remaining to be further explored (Wang, 2014 ; Hinchet et al, 2015 ; Wang S. et al, 2015 ; Zhang et al, 2015 ; Zhu et al, 2015 ; Zhang B. et al, 2016 ; Pu et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%